2000
DOI: 10.1021/jo000978e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6H-Indolo[2,3-b][1,6]naphthyridines and Related Compounds as the 5-Aza Analogues of Ellipticine Alkaloids

Abstract: Treatment of 2-(1-alkynyl)phenyl isocyanates 6 with the iminophosphorane 14 produced in situ the benzoenynyl carbodiimides 15. Thermolysis of 15 under refluxing p-xylene furnished the 6H-indolo[2,3-b][1,6]naphthyridines 5, which could be regarded as the 5-aza analogues of ellipticine alkaloids. Similarly, condensation of 6 with the iminophosphorane 20 led to the formation of the 6H-indolo[2,3-b][1,5]naphthyridines 25 as the major isomer and the 10H- indolo[2,3-b][1,7]naphthyridines 26 as the minor isomer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 38 publications
0
50
0
1
Order By: Relevance
“…In the calculation of the structure of 12B, the bond distance between O and P was 2.943 Å, and this lies midway between O-P covalent bond (1.79 Å) and van der Waals radius of O and P (3.30 Å). It is reported that phospa-oxa-azulene (14) showed the bond lengths 2.00-2.36 Å. [22][23][24] Although the bond distance of 12B is longer than those of 14, above results suggest that 12 exists as resonance hybrid of 12B.…”
Section: ------------------------------------------------------------mentioning
confidence: 73%
See 2 more Smart Citations
“…In the calculation of the structure of 12B, the bond distance between O and P was 2.943 Å, and this lies midway between O-P covalent bond (1.79 Å) and van der Waals radius of O and P (3.30 Å). It is reported that phospa-oxa-azulene (14) showed the bond lengths 2.00-2.36 Å. [22][23][24] Although the bond distance of 12B is longer than those of 14, above results suggest that 12 exists as resonance hybrid of 12B.…”
Section: ------------------------------------------------------------mentioning
confidence: 73%
“…We previously reported that reaction of 2-(triphenylphosphoimino)-1-azaazulene with aryl isocyanate proceeded via 2-aryl 1-azaazulen-2-yl carbodiimide intermediate. It is known that enyne-carbodiimides proceeded cyclization to give heteroaromatics such as carbolines and ellipticine analogues, [11][12][13][14][15][16][17] and underwent Pouson-Khand type reaction in the presence of Mo(CO) 6 . 26 Therefore, we next examined the reaction of 8 with aryl isocyanate.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbodiimide is considered to be an aza-equivalent of allene, and more importantly, canceled dipole moments of C-N bonds are expected to facilitate the homolytic cleavage of the C-N bond to form radical species. The Wang [24][25][26][27][28] and the Schmittel 29-31) groups have recently reported the thermal CA of AYCs, but their scopes are limited to conjugated systems, whose electronic and steric environments are far different from nonconjugated ones, and which would be unable to provide dibenzonaphthyridine derivatives. Herein, we report the synthesis and the CA reactions of AYCs 1 and 2.…”
Section: )mentioning
confidence: 99%
“…The synthesis of the 1-chloro-5-aza-ellipticine (7) was accomplished in six steps with a 6.7% overall yield (Scheme 1) using a modification of the procedure developed by Zhang et al 7,14,15 The precursor 4 16 was converted to the isocyanate 5 using triphosgene. 17 The radical cycloaddition of 5 with phosphorane 6 occurs at elevated temperature and is accompanied by precipitation of triphenylphosphine oxide.…”
mentioning
confidence: 99%